2018
DOI: 10.1177/1591019918800458
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the results of intradiscal ozone injection to treat different types of intervertebral disc herniation based on MSU classification

Abstract: Purpose To evaluate the therapeutic efficacy of intradiscal ozone injection in reducing pain and improving patients’ performance in different types of intervertebral disc herniation based on Michigan State University (MSU) classification. Patients and methods Consecutive patients with low back pain and radiculopathy treated in our center with ozone chemonucleolysis from May 2017 through to January 2018 ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(63 reference statements)
1
4
0
Order By: Relevance
“…15 The disk herniation type 2AB was set as reference value in our population because it was associated with the worst outcome after OCN. This finding is in line with the previously cited article by Hosseini et al 27 where the authors found a worse result in 2AB group, probably because of the bigger size of herniation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…15 The disk herniation type 2AB was set as reference value in our population because it was associated with the worst outcome after OCN. This finding is in line with the previously cited article by Hosseini et al 27 where the authors found a worse result in 2AB group, probably because of the bigger size of herniation.…”
Section: Discussionsupporting
confidence: 92%
“…Hosseini et al, 27 recently reported that the reduction in NRS and ODI improvement after OCN is different if the MSU classification is considered. These authors reported a worse outcome in herniated disk types 1C, 2C, and 2AB.…”
Section: Discussionmentioning
confidence: 99%
“…Hosseini et al(2019) performed oxygen-ozone chemonucleolysis on a large number of patients with lumbar disc herniation and registered a high success rate at all types of disc herniation and failed back surgery [ 32 ]. Also several meta-analyses were published indicating the efficacy of intradiscal ozone injection in patients with disc prolapse [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ozone can be administered as a gas mixture of oxygen-ozone (medical-grade ozone), with a concentration between 10 and 40 µg/mL [23][24][25][26] . However, a study on the therapy with low (10 µg/mL), medium (40 µg/mL), and high (60 µg/mL) concentrations in patients with disc herniation showed a higher rate of decline in the group who received a volume of 40 µg/ml 25.…”
Section: Types Of Administration Doses and Concentrationsmentioning
confidence: 99%
“…However, a study on the therapy with low (10 µg/mL), medium (40 µg/mL), and high (60 µg/mL) concentrations in patients with disc herniation showed a higher rate of decline in the group who received a volume of 40 µg/ml 25. 26 . Table 1 summarizes the studies considered for long-term results.…”
Section: Types Of Administration Doses and Concentrationsmentioning
confidence: 99%